Peptide arrays for development of PDGFRβ affine molecules - Marr, Annabell; Nissen, Felix; Maisch, Daniel; Altmann, Annette; Rana, Shoaib; Debus, Jürgen; Huber, Peter E.; Haberkorn, Uwe; Askoxylakis, Vasileios (Molecular imaging & biology, 2013)
Peptide arrays represent an attractive method for identification of amino acid motifs that bind to target structures. Spotting derivatives of the linear peptide platelet-derived growth factor receptor (PDGFR)-P1, which has been identified to bind the extracellular domain of the platelet-derived growth factor receptor beta, allows the synchronous investigation of the target affinity of numerous ligands.
Gesehen am 23.06.2021